On the relative importance of bending and compression in cervical spine bilateral facet dislocation. (April 2019) - Nightingale, Roger W.; Bass, Cameron R.; Myers, Barry S.
Abstract: Background: Cervical bilateral facet dislocations are among the most devastating spine injuries in terms of likelihood of severe neurological sequelae. More than half of patients with tetraparesis had sustained some form of bilateral facet fracture dislocation. They can occur at any level of the sub-axial cervical spine, but predominate between C5 and C7. The mechanism of these injuries has long been thought to be forceful flexion of the chin towards the chest. This "hyperflexion" hypothesis comports well with intuition and it has become dogma in the clinical literature. However, biomechanical studies of the human cervical spine have had little success in producing this clinically common and devastating injury in a flexion mode of loading. Methods: The purpose of this manuscript is to review the clinical and engineering literature on the biomechanics of bilateral facet dislocations and to describe the mechanical reasons for the causal role of compression, and the limited role of head flexion, in producing bilateral facet dislocations. Findings: Bilateral facet dislocations have only been produced in experiments where compression is the primary loading mode. To date, no biomechanical study has produced bilateral facet dislocations in a whole spine by bending. Yet the notion that it is primarily a hyper-flexion injury persists in the clinical literature. Interpretation: Compression and compressive buckling are the primary causes of bilateral facet dislocations. It is important to stop using the hyper-flexion nomenclature to describe this class of cervical spines injuries because it may have a detrimental effect on designs for injury prevention. Highlights: Cervical spine bilateral facet dislocations have long been thought to be caused by hyperflexion. There has been almost no biomechanical evidence to support this mechanism. In fact, bilateral facet dislocations are most likely caused by compressive buckling. Mischaracterizing the mechanism of this catastrophic injury compromises the development of mitigation technologies